Lesson Study: Cultivation Of Professional Learning Community (PLC) In The Institute Of Teacher Education (IPG) In Negeri Sembilan Malaysia - Abdullah, Hasnah; Ibrahim, Mohd Ashraf; Malek, Manoriza Abdul (Journal of Learning Improvement and Lesson Study, 2022)
Professional Learning Community (PLC) is a platform that is recognizable to the development of professionalism among educators as well as the aspects of teaching and learning of educators. A professional learning community, or PLC, is a group of educators that meets regularly, shares expertise, and works collaboratively to improve teaching skills and the academic performance of students. Therefore, an initiative has been taken by the Institute of Teacher Education Malaysia (IPGM) to cultivate PLC among teacher educators in all 27 IPGs in Malaysia. One of the collaborative tools recommended for its application is Lesson Study (LS). LS is seen as a collaborative tool that focuses on student learning and is implemented collaboratively. A study was conducted by applying LS in the Teaching and Learning process (PdP) at Raja Melewar Teacher Education Institute to student teachers in the Post -Education Diploma Program (PDPP) for Philosophy and Educational Development in Malaysia (EDUP2072). The students involved are students majoring in History and TESL. A total of two cycles were implemented and the results of each cycle were shared with fellow teacher educators and given improvements before the implementation of the 2nd cycle. Observations were carried out during the TnL process by seven fellow teacher educators as well as one expert. A reflection session was held immediately after the end of each TnL and discussed. The results of the study found that i. LS can provide an impact on student learning towards better understanding and clarity, ii. Collaboration between teacher educators can produce a healthy culture in the organization and iii. Cultivation of LS among teacher educators can promote the cultivation of PLC in Teacher Education Institutes in Malaysia. Overall LS and KPP should be given focus by all instructional leaders in Teacher Education Institutes and The Institute of Teacher Education Malaysia (IPGM) as a culture and in an effort to develop the professionalism of teacher educators.